Pengaruh Co-Branding Ventela dengan Mantappu Jiwa by Jerome Polin terhadap Keputusan Pembelian Sepatu Ventela Konnijiwa: (Survei pada followers Instagram @ventelashoes) - Yulia Rahmawati; Jamiati KN (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The rapid growth of local brands in Indonesia's fashion industry is driven by the use of online media as a promotional platform. One notable brand is Ventela, which employs a co-branding strategy to capture market attention. This study aims to analyze the implementation of co-branding by @ventelashoes on Instagram, evaluate consumer purchasing decisions regarding Ventela Konnijiwa shoes, and measure the extent to which the co-branding collaboration between Ventela and Mantappu Jiwa by Jerome Polin influences purchasing decisions. The study applies co-branding theory, which includes dimensions such as brand awareness, brand strength, mutual benefits, uniqueness of collaboration, as well as positive consumer judgment and response. Meanwhile, the purchasing decision process is analyzed through five stages: problem recognition, information search, evaluation of alternatives, purchase decision, and post-purchase behavior. A quantitative approach was used in this study through a survey method, with data collected from 133 followers of the @ventelashoes Instagram account using a random sampling technique. The results indicate that the co-branding between Ventela and Mantappu Jiwa received a positive response from the respondents. The influence of co-branding on purchasing decisions is strong, with a correlation value of 0.904. Co-branding contributes 81.8% to the purchasing decision of Ventela Konnijiwa shoes, while the remaining 18.2% is influenced by other factors.